Impact of Climate Change on Norway Spruce Flowering in the Southern Part of the Western Carpathians - Škvareninová, Jana; Mrekaj, Ivan (Frontiers in Ecology and Evolution, 2022)
This work presents the impact of climate change on full flowering (BBCH 65) in Norway spruce (Picea abies (L.) Karst.) at 54 phenological stations over two 30-year-long periods, from 1961 to 1990 and from 1991 to 2020. The stations were located in 10 protected areas (protected landscape area, national park) at elevations from 390 to 1400 m a.s.l. We analysed the changes in average onset of full flowering, trends of the phase, phenological altitudinal gradient, and correlations of flowering to monthly climatological standard normals of air temperature and sum of precipitation. The impact of climate change was observed in the second period, when flowering started 4–8 days earlier. The phenophase was shortened by 4 days in comparison to the first period, and the shift of the significant trend occurred 7 days earlier. The phenological altitudinal gradient did not substantially change. The analysis of the temperature impact on flowering showed an effect of the cold period preceding the onset of the phenological phase on its delayed onset. The change in January temperatures between periods indicated warming by 1.24–1.34°C. The change also occurred in the evaluation of the three-month period when the spring air temperature increased. The mean three-month air temperature (Jan–Mar) increased by 0.82 to 1.1°C in the second period. It was more substantial at lower elevations. The most significant changes in precipitation conditions were observed by the increase in precipitation in March and by the decrease in precipitation between the observed periods in April. The results of all indicators for Norway spruce flowering in the second period indicated changes in climatic conditions in the region.